Hemispheric dispersion of radioactive plume laced with fission nuclides from the Fukushima nuclear event - Hsu, Shih-Chieh; Huh, Chih-An; Chan, Chuen-Yu; Lin, Shuen-Hsin; Lin, Fei-Jan; Liu, Shaw Chen (American Geophysical Union, 2012)
Radioactivities of particulate 131I and 137Cs released from the Fukushima nuclear accident were monitored in a regional aerosol network including two high mountain sites (central Taiwan and Tibetan Plateau). The results were integrated with data measured elsewhere around the world, with special focus on the mid-latitudes. The hemispheric transport of the Fukushima radiation clouds (FRCs) by the westerlies took $18 days, displaying an exponential-like decrease eastward, with a dilution factor of at least five orders of magnitude following a full circuit around the globe. The initial two waves of FRCs may travel at different atitudes: the first one at $3–4 km, whereas the second one up to 5 km or more. 131I and 137Cs were fractionated during transport, with 137Cs concentrated in the shallower layer, susceptible to depositional removal, while 131I moving faster and higher. This accident may be exemplified to identify some atmospheric processes on the hemispheric scale.